THE PREVALENCE OF SARCOMA IN LATVIA DEPENDING ON GENDER AND AGE OVER A 10-YEAR PERIOD - Degtjarjovs, Iļja; Degtjarjova, Natalija; Sargsjane, Jeļena; Šakina, Silvija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Sarcomas are a heterogeneous group of malignant neoplasms that arise from the mesenchymal tissues, including bone, cartilage, fat, muscle, blood vessels, nerves, and deep skin tissues. The World Health Organization (WHO) Classification of Tumors of Soft Tissue and Bone encompasses over 80 distinct histologic subtypes of sarcomas, each with unique morphologic and molecular features. The high degree of histologic diversity among sarcomas underlies their capacity to arise in virtually any anatomic site. Sarcomas represent a relatively uncommon form of cancer, accounting for less than 1% of all new cancer diagnoses in adults and approximately 15% in children. The global incidence of sarcomas is estimated to be approximately 8 cases per million per year for bone sarcomas and 30 cases per million per year for soft tissue sarcomas. The objectives of the study to provide a comprehensive overview of the gender and age differences in the epidemiology of sarcomas in Latvia across 10 years. This retrospective population-based study draws on epidemiological data regarding cases of bone sarcomas and soft tissue sarcomas collected by the pathological registry of the hospital of Traumatology and Orthopaedics. From 2012 to 2022, 146 new cases of sarcoma were diagnosed in Latvia. Of these, 74 (50.7%) were men and 72 (49.3%) were women. The average annual number of new cases was 6.73 for men and 6.55 for women. The age-standardized incidence rate per 100,000 people per year was 0.8 for men and 0.5 for women. The youngest patient was 14 years old and the oldest was 87 years old. The most common age group for the sarcomas was between 61-70 years old (19.2%). The study found that the incidence of sarcomas in Latvia was higher in males than in females, and that the incidence was highest in 2020 and lowest in 2016.